2019
DOI: 10.3390/s19102376
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of UVB Irradiation and Oxidative Stress on the Skin Barrier—A New Method to Evaluate Sun Protection Factor Based on Electrical Impedance Spectroscopy

Abstract: Sunlight is vital for several biochemical processes of the skin organ. However, acute or chronic exposure to ultraviolet radiation (UVR) has several harmful effects on the skin structure and function, especially in the case of the failing function of antioxidative enzymes, which may lead to substantial tissue damage due to the increased presence of reactive oxygen species (ROS). The aim of this work was to investigate the combined effect of ultraviolet B (UVB) irradiation and oxidative stress on the skin barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…For this, an equivalent circuit comprised of a resistor, for solution resistance, connected in series with the skin membrane impedance was used. The skin membrane impedance was modelled by a parallel combination of a resistor for the skin membrane resistance, R mem , and a so-called constant phase element, CPE, which here represents the capacitive properties of the skin membrane [20][21][22] . A more detailed description of Franz cell equipped with four electrodes for measurement of skin membrane resistance can be found elsewhere 20 .…”
Section: Methodsmentioning
confidence: 99%
“…For this, an equivalent circuit comprised of a resistor, for solution resistance, connected in series with the skin membrane impedance was used. The skin membrane impedance was modelled by a parallel combination of a resistor for the skin membrane resistance, R mem , and a so-called constant phase element, CPE, which here represents the capacitive properties of the skin membrane [20][21][22] . A more detailed description of Franz cell equipped with four electrodes for measurement of skin membrane resistance can be found elsewhere 20 .…”
Section: Methodsmentioning
confidence: 99%
“…This caveat should be kept in mind for the 1 kHz data obtained with the NE. Still, it was decided to use this parameter due to the fact that it can be straightforwardly compared with the data obtained with the 4E methodology, where the 1 kHz data represent the skin membrane resistance in a consistent and well established manner 9,39,40 . Further, previous measurements performed with a noninvasive Nevisense probe showed that the NE impedance data can be expressed as the ratio of the impedance magnitudes at two particular frequencies of 20 and 500 kHz, which greatly reduces the complexity of the experimental data 38 .…”
Section: In Vitro Experiments With Nevisense (Ne) and Dermalab Hydratmentioning
confidence: 99%
“…One potential candidate is the pharmacologically active-but nonpsychoactive-antioxidant and anti-inflammatory phytocannabinoid-cannabidiol (CBD, Figure 1) found in the Cannabis sativa L. plant [8][9][10]. Assessment of the antioxidant activity of CBD has shown that it can regulate the redox state directly by influencing redox components and indirectly interacting with other molecular targets related to redox balance [11].…”
Section: Introductionmentioning
confidence: 99%